Corporate Restructuring in Response to Performance Decline: Impact of Ownership, Governance and Lenders - Lai, Jim; Sudarsanam, Sudi (Review of Finance, 1997)
Abstract Firms in performance decline may choose a variety of restructuring strategies for recovery with conflicting welfare implications for different stakeholders such as shareholders, lenders and managers. Choice of recovery strategies is therefore determined by the complex interplay of ownership structure, corporate governance and lender monitoring of such firms. For a sample of 297 U.K. firms experiencing relative stock return decline during 1987–93, we examine the impact of these factors as well as other control factors on their turnaround strategies. Strategy choices during the decline year and two post-decline years are modelled with logit regressions. Our results show that turnaround strategy choices are significantly influenced by both agency and control variables. While there is agreement among stakeholders on certain strategies there is also evidence of conflict of interests among them. Thereis further evidence of shifting coalitions of stakeholders for or against certain strategies.